Context-specific components of a training programme for cost centre managers in a public hospital in Limpopo Province, South Africa - Mothiba, T. M.; Jooste, K.; Nolte, A. G. W. (My University, 2014)
The purpose of the study was to determine the context-specific components of a training programme for cost centre managers in a public hospital in Limpopo Province, South Africa. A qualitative, descriptive, exploratory and contextual research design was used. Homogenous purposive sampling was conducted from a population of 36 nurse managers appointed as cost centre managers. One focus group discussion comprising nine cost centre managers and twelve cost centre managers participated in unstructured one-on-one interviews until data saturation was reached. Data were analysed qualitatively using Teschs’ open coding method. The findings revealed that there is a need for context-specific training programme which is relevant to the public hospital and the content for the programme must address the needs of cost centre managers. It was recommended that the programme should indicate the nature of activities that would be included in the new programme and the development should be based on a needs assessment of the people who were going to be trained. A needs assessment is important before decisions are taken about the type of activities and their instructional arrangements to be included in the programme.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:1 (June), 2014, pp. 437-447.
Keywords: Hospital training programmes; Public hospitals; Hospitals - Business management; Hospital administration